PENGARUH KEPEMIMPINAN LURAH TERHADAP DISIPLIN KERJA PEGAWAI PADA KANTOR KELURAHAN LOA BAKUNG KECAMATAN SUNGAI KUNJANG - ., Mulyadi (PREDIKSI, 2012)
This study is verification or the nature of causality, ie a study to find the relationship between the variables because the variable effect. The relationship in question is the relationship between the leadership of the village chief (Independent variable) with work discipline (Dependent variable). Study entitled headman leadership influence on employee discipline at sub-district office Loa Bakung Sungai Kunjang. Formulation of the research problem is how far the influence of urban village leadership to discipline employees working at sub-district office loa daffodil Kunjang river. In this study the authors will use two kinds of data collection techniques, namely: Library Research and Field Work Research. Measurement scale used is the Likert scale, the calculation formulation used is Coefficient Product Moment.